Topics on the Na+/Ca2+ Exchanger: Involvement of Na+/Ca2+ Exchange System in Cardiac Triggered Activity - Nobuo Homma; Md Shah Amran; Yoshinobu Nagasawa; Keitaro Hashimoto (Elsevier, 2006)
Sodium-calcium exchange (NCX) is one of the major regulators of intracellular Ca2+ concentration in cardiac myocytes. The bi-directional and electrogenic property of NCX raises a question about whether NCX is involved in arrhythmias. We reviewed the role of NCX in cardiac triggered activity in limited experimental conditions: the digitalis-induced arrhythmia, the arrhythmia caused from sustained opening of sodium channel, and the arrhythmia caused from the inhibition of inwardly rectifying potassium current. Effects of NCX inhibitors on ventricular arrhythmias recorded on ECG or the delayed afterdepolarizations and triggered activity recorded by the current clamp method were evaluated. As an NCX inhibitor, we preferred to use SEA0400 instead of KB-R 7943. For a precise analysis, a computational reconstruction of action potential with the Luo and Rudy model was applied. The cardiac NCX system seems to play a role only in the digitalis-induced arrhythmia and may not be involved in other arrhythmias. This review highlights the relationship between triggered activity and an NCX system and also suggests the physiologic and pathologic aspect of the NCX system in cardiac arrhythmias. Keywords:: Na+/Ca2+ exchanger, triggered activity action potential, cardiac myocyte, simulation